Electrophilicity of neutral square-planar organosilver(iii) compounds. Issue 28 (6th March 2023) - Joven-Sancho, Daniel; Demonti, Luca; Martín, Antonio; Saffon-Merceron, Nathalie; Nebra, Noel; Baya, Miguel; Menjón, Babil
Abstract : Neutral silver(iii ) compounds stabilised with just monodentate ligands are found to exhibit a distinct tendency to associate an additional ligand at the apical position. They include the first documented compound with a Ag(iii )–As bond. Abstract : Neutral Ag(iii ) complexes stabilised with just monodentate ligands are here unambiguously established. In a series of square-planar (CF3 )3 Ag(L) compounds with hard and soft Group 15 donor ligands, L, the metal center has been found to exhibit substantial acidity favouring apical coordination of an additional ligand under no coordination constraints.